Career preferences of graduating medical students in China: a nationwide cross-sectional study. Issue 1 (December 2016) - Hou, Jianlin; Xu, Maoyi; Kolars, Joseph; Dong, Zhe; Wang, Weimin; Huang, Amy; Ke, Yang
Abstract Background China faces major challenges in the distribution of health professionals with serious shortages in rural areas and in the development of Primary Care Providers (PCPs). This study investigates the career preferences of medical students in China and the impact of rural backgrounds on these preferences. Methods Medical students in the final year of their program in 16 medical schools across China completed a 58-item survey that included questions regarding their demographic characteristics, attitudes toward practice in low resource areas, postgraduate planning, self-assessed competency, university facilities assessment, and financial situation. Descriptive calculation and Logit model were used for the analysis. Results Completed surveys from 3020 students were included in the analysis. Upon graduation, 48.5 % of the medical students preferred to work in urban public hospitals and this percentage rose to 73.6 % when students were asked to state their anticipated preference five years after graduation. Students' top three ranked reasons for preferred careers were "good career prospects", "living close to parents/families", and "remuneration". Those who preferred to work in rural areas upon graduation were more likely to be those who lived in rural areas when 1–15 years old (β = 2.05, p  < 0.001), had high school in rural areas (β = 1.73, p  < 0.001), or had parents' place of current residence in rural areas (β = 2.12, p  < 0.001). Similar results were found for those students who preferred to work in PCPs. Conclusions To address the serious shortages of health professionals in rural areas and PCPs, medical schools should consider strategies to recruit more medical applicants with rural backgrounds and to orient students to rural and primary care interests.